Tindak Tutur Penolakan Ekspresif dalam Bahasa Dayak Maanyan Paju Epat di Desa Sababilah - Marchiananda Putri; Albertus Purwaka; linggua Sanjaya Usop; Indra Perdana; Misnawati Misnawati (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2023)
Rejection is a speech delivered by the interlocutor as a rejection reaction to the speech spoken by another person. Rejection utterances will be threatening and slap the speaker's face if delivered with impolite sentences. This research was conducted to find out the forms of speech acts of refusal in the Dayak Maanyan language. Based on the research, the research results obtained by the researcher are (1) There are five forms of speech acts of refusal in Ma'anyan Dayak language in residential areas, namely: (a) expressive refusal speech acts using the word puang 'no' in Ma'anyan language (b ) expressive refusal speech acts using reasons in Ma'anyan language, (c) expressive refusal speech acts using thank you in Ma'anyan language, (d) expressive refusal speech acts using praise in Ma'anyan language, (e) expressive refusal speech acts using criticism in Ma'anyan. This is caused by the context spoken by the interlocutor. The most frequent speech acts are caused by the influence of the age of the interlocutor and also the topic of conversation triggers rejection.